Prevalence of treated and untreated groin hernia in eastern Uganda. Issue 6 (20th March 2014) - Löfgren, J; Makumbi, F; Galiwango, E; Nordin, P; Ibingira, C; Forsberg, B C; Wladis, A
Abstract: Background: Hernia repair is the most commonly performed general surgical procedure worldwide. The prevalence is poorly described in many areas, and access to surgery may not be met in low- and middle-income countries. The objectives of this study were to investigate the prevalence of groin hernia and the surgical repair rate in a defined sub-Saharan region of Africa. Methods: A two-part study on hernia prevalence was carried out in eastern Uganda. The first was a population-based prevalence study with 900 randomly selected men in a Health and Demographic Surveillance Site. The second was a prospective facility-based study of all surgical procedures performed in the two hospitals providing surgical care in the region. Results: The overall prevalence of groin hernia (current hernia or scar after groin hernia surgery) in men was 9·4 per cent. Less than one-third of men with a hernia had been operated on. More than half had no pain symptoms. The youngest age group had an overall prevalence of 2·4 per cent, which increased to 7·9 per cent in the age range 35–54 years, and to 37 per cent among those aged 55 years and above. The groin hernia surgery rate at the hospitals investigated was 17 per 100 000 population per year, which corresponds to a surgical correction rate of less than 1 per cent per year. Based on hospital records, a considerable number of patients having surgery for groin hernia were women (20 of 84 patients, 24 per cent). Conclusion: Groin hernia is a common condition in men in this east Ugandan cohort and the annual surgical correction rate is low. Investment is needed to increase surgical capacity in this healthcare system. Abstract : High prevalence, low surgery rate